A comparison between intensive and conventional cabergoline treatment of newly diagnosed patients with macroprolactinoma. (2nd July 2013) - Rastogi, Ashu; Bhansali, Anil; Dutta, Pinaki; Singh, Paramjit; Vijaivergiya, Rajesh; Gupta, Vaishali; Sachdeva, Naresh; Bhadada, Sanjay Kumar; Walia, Rama
Summary Context Intensive treatment with cabergoline may lead to earlier reduction in prolactin and tumour volume in comparison to conventional schedule. Objective To compare the efficacy and safety of two different dosing schedules of cabergoline in patients with macroprolactinoma. Design Prospective, randomized trial in drug naive patients assigned to conventional (4 weekly escalation by 0·5 mg per week, group A) or intensive (weekly increase by 1 mg per week followed by 4 weekly escalation, group B) treatment with cabergoline. Outcome measure The duration required to achieve normoprolactinemia and tumour shrinkage of >50% as a composite end‐point. Results 38 patients (19 in each group) completed the study with a mean follow‐up of 64·3 ± 24·9 weeks. More subjects (22%) achieved the composite end‐point in group B (18/19) as compared to the group A (14/19) (P = 0·18). The duration of cabergoline treatment required to achieve the composite end‐point was 13·1 ± 9·5 weeks vs 19·3 ± 15·7 weeks (P = 0·34) in the group A and B, respectively. A reduction in prolactin of ≥90% by the fourth week of cabergoline therapy predicted subsequent normalization of prolactin (AUC 0·78; P = 0·04). A further increase in cabergoline dosage after normalization of prolactin in patients with tumour reduction of <50%, led to further tumour shrinkage by 31·2% in an additional 26·3% of patients. Conclusions Intensive treatment with cabergoline is not superior to the conventional recommended dosage schedule in respect to the time necessary to achieve normoprolactinemia and ≥50% tumour shrinkage. Clinical trial registry: NCT 01143584.